Analisis Faktor – Faktor Yang Mempengaruhi Underpricing Saham Pada Perusahaan Yang Melakukan Initial Public Offering (IPO) Di Bei Tahun 2020 - 2022 - Nuralifah, Annisa; Purnamasari, Endah Dewi; Wulandari, Try (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
In this instance, the elements that impact underpricing are Return on Assets, Debt to Equity Ratio, Company Age, Underwriter Reputation, and Auditor Reputation. The purpose of this research is to identify and examine these factors. Researchers employ quantitative techniques. A total of 167 firms were included in the research population. Information gathered by directly quoting financial reports from the official IDX website for the three years that the report was available, 2020–2022. Multiple linear regression analysis, classical assumption test analysis, and descriptive analysis approaches were the methods of data analysis employed in this study. The findings of this study include There is no discernible relationship between underpricing and Return on Assets, Debt to Equity Ratio, or Company Age in this instance.